Mangrove Forest Utilization for Sustainable Livelihood through Community-Based Ecotourism in Kao Village of North Halmahera District - Yerik Afrianto Singgalen (Institut Pertanian Bogor (IPB University), 2020)
This article aims to describe the mangrove forest utilization for sustainable livelihood through a community-based ecotourism approach. This research conduct in Kao Village, North Halmahera District of Indonesia. This study was done in a qualitative method using a life-history approach. The data was collected through in-depth interviews, observation, and document study. The data were analyzed using a triangulation method to obtain credible information. These research findings show that cultural value, known as Higaro was able to mobilize the capability to access resources such as natural and social capital. In its development, assimilation and acculturation caused changes in livelihood structure. In addition, The mining sector's existence in the Kao community custom area had the potential to limit access to natural and social capital due to ecological loss. However, the mining sector could mobilize human and physical capital through Social Performance programs in the education sector and infrastructure development. The adverse effects of the mining sector to the environment had become such a stimulus for the Kao Village community to adopt an environmentally friendly development approach that had economic value and was able to improve the community welfare. Thus, the Kao Village community managed to maintain and utilize the mangrove forest using a community-based ecotourism approach to endurance livelihood sustainability. These results could be developed into recommendations for regional policymakers, especially in the rural areas, to mobilize the capability of local community access to capitals through the tourism sector to maintain livelihood sustainability.